Management of Isolated Radial Diaphyseal Fractures in the Paediatric Population - Asnaf Siddique, Sara Jadoon, Tauseef Raza, Nasrul Huda, Junaid Javaid, Zia Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Radial diaphyseal fractures are common in the pediatric population due to high activity levels and physical play. These fractures can occur due to trauma, and their management is crucial to ensure proper healing and prevent long-term complications. Objective: To evaluate the management approaches for isolated radial diaphyseal fractures in the pediatric population and determine their clinical outcomes. Methodology: This prospective cohort study was conducted at Latamber Type D Hospital district karak during january 2022 to march 2023. including 95 pediatric patients diagnosed with isolated radial diaphyseal fractures, evaluating management strategies and treatment outcomes. Results: The study found that 60% of pediatric patients with isolated radial diaphyseal fractures were treated conservatively and 40% surgically. The conservative group had a mean recovery time of 6.0 weeks, while the surgical group had 8.0 weeks (p = 0.02). Complications were low, with non-union occurring in 2% (all surgical), malunion in 3%, and infection in 1% (all surgical). Ninety percent achieved full range of motion, and 70% returned to normal activities within 6 weeks, with better outcomes in the conservative group. Both treatment methods were effective with minimal complications. Conclusion: Both conservative and surgical management of isolated radial diaphyseal fractures in the pediatric population yielded positive outcomes. Conservative treatment is effective for most cases, but surgical intervention may be required for more severe fractures or those with significant displacement. Proper management results in good functional recovery, with low complication rates. Keywords: Radial diaphyseal fractures, pediatric fractures, conservative management, surgical intervention, recovery outcomes.